Determination of Sulfacetamide Sodium in Pure and Their Pharmaceutical Formulations by Using Cloud Point Extraction Method - Nisreen jassam Alaallah; Saadiyah Ahmad Dhahir; Hameed Hussein Ali (مجلة بغداد للعلوم)
In this study, simple, low cost, precise and speed spectrophotometric methods development for evaluation of sulfacetamide sodium are described. The primary approach contains conversion of sulfacetamide sodium to diazonium salt followed by a reaction with p-cresol as a reagent in the alkaline media.  The colored product has an orange colour with absorbance at λmax 450 nm. At the concentration range of (5.0-100 µg.mL-1), the Beer̆ s Low is obeyed with correlation coefficient (R2= 0.9996), limit of detection as 0.2142 µg.mL-1, limit of quantification as 0.707 µg.mL-1 and molar absorptivity as 1488.249 L.mol-1.cm-1. The other approach, cloud point extraction was utilized to an estimation of a trace amount of the colored product in the previous procedure followed by a measuring process with a UV-Vis spectrophotometer. The linearity of the calibration graph was above the range of (1.0-60 µg.mL-1), the correlation coefficient (R2= 0.9991) and molar absorptivity was 7417.622 L.mol-1.cm-1. The detection limit(LOD) and quantification limit(LOQ) were based to be  0.070 and 0.231 µg.mL-1 , respectively. This approach was successfully employed for sulfacetamide sodium detection within the pure and pharmaceutical formulation.